7α-Hydroxy-β-Sitosterol from Chisocheton tomentosus Induces Apoptosis via Dysregulation of Cellular Bax/Bcl-2 Ratio and Cell Cycle Arrest by Downregulating ERK1/2 Activation. (11th September 2012) - Tasyriq, Mohammad; Najmuldeen, Ibrahim A.; In, Lionel L. A.; Mohamad, Khalit; Awang, Khalijah; Hasima, Noor
Abstract : In continuation of our interest towards the elucidation of apoptotic pathways of cytotoxic phytocompounds, we have embarked upon a study on the anticancer effects of 7 α -hydroxy- β -sitosterol (CT1), a rare natural phytosterol oxide isolated from Chisocheton tomentosus . CT1 was found to be cytotoxic on three different human tumor cell lines with minimal effects on normal cell controls, where cell viability levels were maintained ≥80% upon treatment. Our results showed that cell death in MCF-7 breast tumor cells was achieved through the induction of apoptosis via downregulation of the ERK1/2 signaling pathway. CT1 was also found to increase proapoptotic Bax protein levels, while decreasing anti-apoptotic Bcl-2 protein levels, suggesting the involvement of the intrinsic pathway. Reduced levels of initiator procaspase-9 and executioner procaspase-3 were also observed following CT1 exposure, confirming the involvement of cytochrome c-mediated apoptosis via the mitochondrial pathway. These results demonstrated the cytotoxic and apoptotic ability of 7 α -hydroxy- β -sitosterol and suggest its potential anti-cancer use particularly on breast adenocarcinoma cells.